Motivações e tempo ao voluntariado: análise de fatores para a gestão em OSCs de direitos sociais no Estado da Paraíba - Alves, Jardel Augusto Gomes Rodrigues (2019)
This research is presented in order to analyze the association between altruistic motivations and the influence that this factor exerts on volunteers and could explain the amount of time they devote to volunteer activities. Adapting a theoretical model developed by Shantz et al. (2014), and analyzing information reported by a sample of 142 volunteers, participants in 19 different Civil Society Organizations that deal with issues related to Social Rights, in the state of Paraíba, was found a positive association between Altruism, Commitment to beneficiaries, Engagement with the volunteer activity and the time dedicated to volunteering. To achieve these conclusions, was developed a quantitative analysis of Exploratory Factor Analysis and also Confirmatory Factor Analysis, through the Modeling of Structural Equations, following the theoretical foundations pointed out by Hair et al. (2009). Results also showed that for the sample studied here, the Commitment does not influence the Engagement, while this second factor exerts influence at a certain level on the amount of time that is dedicated to volunteering. These findings provide a new perspective on the link between volunteers’ motivation and active participation in volunteer activities. Practical implications for practice and future research directions are suggested.